Two new species of the genus Laemostenus Bonelli sg. Antisphodrus Schaufuss from Turkey (Coleoptera: Carabidae: Sphodrini) - Lohaj, Roman; Anlaş, Sinan (Zootaxa, 2021)
Two new species of the genus Laemostenus Bonelli sg. Antisphodrus Schaufuss of the bodemeyeri species-group are described, illustrated and compared with the related species: Laemostenus (Antisphodrus) bozdagensis sp. nov. (Type locality Manisa, Bozdağlar) and Laemostenus (Antisphodrus) binboga sp. nov. (Type locality Kayseri, Sarız, Binboğa Dağları). These new species were collected with subterranean pitfall traps in the mesovoid shallow substratum (MSS). Additional faunistic and systematic comments, identification key and check-list for Turkish species of the bodemeyeri species group are also presented. Distribution of the bodemeyeri species group is mapped.